Piperine Increases Pentagamavunon-1 Anti-cancer Activity on 4T1 Breast Cancer Through Mitotic Catastrophe Mechanism and Senescence with Sharing Targeting on Mitotic Regulatory Proteins - Endah, Endah (Brieflands, 2022)
Pentagamavunon-1 performs more potent anti-cancer effects than curcumin against various cancer cells, but it remains to be optimized. Piperine shows the activity as an enhancer of a therapeutic agent. This study expects to achieve higher effectiveness of PGV-1 on 4T1 breast cancer cells through co-treatment with piperine with exploring the effect of cytotoxicity, mitotic catastrophe, cellular senescence, and target proteins of PGV-1 and piperine on the regulation of mitosis in TNBC cells (4T1). The assays emphasize MTT assay, May Grünwald-Giemsa staining, SA-β-galactosidase assay, and bioinformatics analysis, respectively, to elicit the respected activities. The results revealed that PGV-1 performed a cytotoxic effect with an IC50 value of 9 µM while piperine showed a lower cytotoxic effect with an IC50 value of 800 µM on 4T1 cells 24 h treatment. However, the combination treatment of both showed a synergistic cytotoxic enhancement effect with an average CI value < 1. Furthermore, the combination of PGV-1 and piperine induced mitotic catastrophe and senescence better than the single treatment. Treatment of 1 µM of PGV-1 and 400 µM of piperine increased the percentage of senescent cells by 33%. Bioinformatics analysis revealed that PGV-1 and piperine target proteins play a role in mitotic regulation, namely CDK1, KIF11, AURKA, AURKB, and PLK1, to contribute to mitotic catastrophe. Therefore, piperine increases the effectiveness of PGV-1 to suppress 4T1 cells growth synergistically that may occur through mitotic catastrophe and senescence targeting on mitotic regulatory proteins.